(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
A convenient method for obtaining of 2,4-disubstituted-2-ethoxycarbonyl-4- pentanolids by means of cyclization using saturated sulfuric acid has been suggested. It has been shown that 3,8-dimethyl-3,8-dialkil-2,7-dioxaspiro[4,4] nonan-l,6-diones are formed as a result of cyclization of dialkenilmalonig esters. Optimal conditions of cyclization have been worked out which provide high yields of goaled products.